Solve: 13-(-3)+(-4)?12-(-2)-2 | Integer Operations with Multiple Signs

Question

Fill in the missing sign (?):

13(3)+(4)?12(2)2 13-(-3)+(-4)?12-(-2)-2

Video Solution

Solution Steps

00:00 Choose the appropriate sign
00:04 Negative multiplied by negative always equals positive
00:07 Let's open the parentheses
00:10 Calculate one operation at a time from left to right
00:14 Positive multiplied by negative always equals negative
00:17 Let's open the parentheses
00:20 Let's continue calculating, this is the solution for the left side, now let's move to the right
00:25 Negative multiplied by negative always equals positive
00:28 Let's open the parentheses
00:32 Calculate one operation at a time
00:37 This is the solution for the right side
00:41 And this is the solution to the question

Step-by-Step Solution

Let's solve the left side first, remembering the following rules:

(x)=+x -(-x)=+x

+(x)=x +(-x)=-x

Now, let's rewrite the expression in the appropriate form:

13+34= 13+3-4=

Let's now solve the expression from left to right:

13+3=16 13+3=16

164=12 16-4=12

Next, we will solve the right-hand side, using the laws we covered earlier.

Let's now rewrite the expression in the appropriate form:

12+22= 12+2-2=

Now, we can solve the expression from left to right:

12+2=14 12+2=14

142=12 14-2=12

Since both sides are equal, the appropriate sign is:

12=12 12=12

Answer

= =